The Relationship Between Environmental Worldviews, Emotions and Personal Efficacy in Climate Change - Ramkissoon, Haywantee; Smith, L. (International Journal of Arts and Sciences, 2014)
This study investigates the effects of a video on the Australian viewers' environmental world views, their emotions and personal efficacy in climate change. Confirmatory factor analysis and structural equation modelling were employed to test the associations between the constructs. The main theoretical contribution relates to the mediating role of emotions in climate change communication. The results show that the video increased viewers' perception that they can influence climate change outcomes, as well as encourage others to reduce the effects of climate change. The findings suggest that effective climate change communication has to target people's emotions. Policy should be directed to climate change communication tools with a focus on emotional engagement to encourage people to take personal responsibility in climate change and act, catalysing the desired behavioural change.